2007
DOI: 10.1016/j.febslet.2007.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Xyr1 receives the lactose induction signal and regulates lactose metabolism in Hypocrea jecorina

Abstract: This study reports the vital regulatory influence of Xyr1 (xylanase regulator 1) on the transcription of hydrolytic enzyme-encoding genes and hydrolase formation on lactose in Hypocrea jecorina. While the transcription of the xyr1 gene itself is achieved by release of carbon catabolite repression, the transcript formation of xyn1 (xylanase 1) is regulated by an additional induction mechanism mediated by lactose. Xyr1 has an important impact on lactose metabolism by directly activating xyl1 (xylose reductase 1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
69
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 31 publications
2
69
0
Order By: Relevance
“…Stricker et al have recently postulated that xyr1 is not regulated by induction but solely by carbon catabolite (de)repression (37). In order to rule out the possibility that the enhanced expression of xyr1 on lactose is due to relief of carbon catabolite repression on this carbon source, we used a ⌬cre1 strain of T. reesei QM 9414, cultivating it under the same conditions as those described above for QM 9414.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stricker et al have recently postulated that xyr1 is not regulated by induction but solely by carbon catabolite (de)repression (37). In order to rule out the possibility that the enhanced expression of xyr1 on lactose is due to relief of carbon catabolite repression on this carbon source, we used a ⌬cre1 strain of T. reesei QM 9414, cultivating it under the same conditions as those described above for QM 9414.…”
Section: Resultsmentioning
confidence: 99%
“…Many of them, therefore, are further induced by the conditions for which they are needed and are degraded once they are no longer needed (40). In contrast, xyr1 expression has been reported to be regulated solely by CRE1-dependent CCR and by repression by the specific transcription factor ACE1, not by induction (19,37). Such a mechanism, if correct, would tightly link xyr1 expression to the flux through carbohydrate catabolism but would preclude the possibility of responding to the presence of a potential inducer.…”
mentioning
confidence: 99%
“…Regulation of the respective genes via Xyr1 is not affected by the substances mediating the induction (degradation and transglycosylation products, such as D-xylose, xylobiose, sophorose as well as the inducer molecule lactose) and is indispensable for all modes of gene expression (Stricker et al 2007a;Stricker et al 2006). Id est, neither the Cre1 (carbon catabolite repressor protein 1)-dependent de-repressed or induced transcriptional level of xyn1 nor the basal or induced transcriptional level of xyn2 could be observed in a Δxyr1 strain.…”
Section: Xyr1 Is the General Activator Of Hydrolase Formation In H Jmentioning
confidence: 99%
“…Several studies have analyzed cellulase and hemicellulase gene expression using RUT C30 as a model strain. [12][13][14][15] Early reports have indicated that RUT C30 harbors the following genetic modifications: (i) a truncation in cre1, which relieves catabolite repression, 16) (ii) a frame-shift in the glucosidase II alpha subunit gene gls2, which increases protein expression, 17) and (iii) an 85-kb deletion in chromosome 2, which deletes a total of 29 genes and is responsible for the truncation of cre1. 18) More recently, LeCrom et al (2009) 19) sequenced the genome of RUT C30 and reported 223 SNPs, but to date, no mutation other than those in cre1 and gls2 has been linked to the hyper-cellulolytic phenotype of RUT C30.…”
Section: Identification Of Major Facilitator Transporters Involved Inmentioning
confidence: 99%